Optimization of the Oil Extraction, Study the Chemical and Physical Properties of Arabica Spent Coffee Grounds - Panpraneecharoen, Sasikarn; Chumanee, Saowapa (Science & Technology Asia, 2020)
This research is to study the extraction of oil from Arabica spent coffee grounds with hexane solvent. The extraction time was 1, 2, 4, 6 and 8 hours by using the soxhlet method. The result found that the 2 hours of 100% n-hexane was the highest yield of 14.42±0.43 g/100g of dry basis. Linoleic acid and palmitic acid were the major fatty acids found in coffee oil. The physical and chemical properties of coffee extracted oil was investigated. The result showed that the FFA was 7.52±1.23%, the peroxide value was 23.96±2.09 mgEqv/kg oil, the density was 1.38±0.04 g/cm3, the viscosity was 34.66±0.41 cSt, the iodine value was 97.25 g I2/100g and the saponification number was 204.12 mgKOH/g. The main functional groups of coffee oil were characterized by using the FTIR spectroscopy.